2019
DOI: 10.3390/ijms20205141
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a Counteracts Glucocorticoid Induction of Bone Loss through Repressing TNFSF13b Modulation of Osteoclastogenesis

Abstract: Glucocorticoid excess escalates osteoclastic resorption, accelerating bone mass loss and microarchitecture damage, which ramps up osteoporosis development. MicroRNA-29a (miR-29a) regulates osteoblast and chondrocyte function; however, the action of miR-29a to osteoclastic activity in the glucocorticoid-induced osteoporotic bone remains elusive. In this study, we showed that transgenic mice overexpressing an miR-29a precursor driven by phosphoglycerate kinase exhibited a minor response to glucocorticoid-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…However, miR-29a-loaded BMSCs-Exos may have direct effects on osteogenesis and/or osteoclastogenesis. Recent studies reported that microRNA-29a can repress osteoclastogenesis to counteract glucocorticoid-induced bone loss ( Wu et al, 2019 ). Lian et al (2019) found that miR-29a regulates PCAF-mediated RANKL and CXCL12 to repress osteoclast formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, miR-29a-loaded BMSCs-Exos may have direct effects on osteogenesis and/or osteoclastogenesis. Recent studies reported that microRNA-29a can repress osteoclastogenesis to counteract glucocorticoid-induced bone loss ( Wu et al, 2019 ). Lian et al (2019) found that miR-29a regulates PCAF-mediated RANKL and CXCL12 to repress osteoclast formation.…”
Section: Discussionmentioning
confidence: 99%
“…GC treatment reduces miR‐29a but not miR‐29b or miR‐29c expression in rat bone and miR‐29a overexpression promotes Runx2 expression and reduces the ability of GCs to inhibit osteoblast differentiation, BMD, and trabecular bone volume 113 . miR‐29a overexpression in mice weakened GCs ability to promote RANKL expression, osteoclast differentiation, and bone erosion, independent of altered OPG expression 110,137 . The mechanisms by which miR‐29a protects the skeleton from GCs may involve miR‐29a inhibiting GC‐induced DKK‐1 expression, which would result in increased Wnt/β‐catenin signaling and osteoblast differentiation 113 .…”
Section: Role Of Mir‐29 Family In Osteoporosismentioning
confidence: 99%
“…The mechanisms by which miR‐29a protects the skeleton from GCs may involve miR‐29a inhibiting GC‐induced DKK‐1 expression, which would result in increased Wnt/β‐catenin signaling and osteoblast differentiation 113 . Alternatively, miR‐29a may delay or inhibit GC induced bone resorption by repressing tumor necrosis factor superfamily 13b expression, which supports osteoclast differentiation and maturation 137 . In conclusion, the consensus across a variety of published studies is that miR‐29s inhibit osteoclast differentiation; this may make it an attractive target to reduce bone resorption in osteoporosis and other skeletal disorders with excessive osteoclastic bone resorption.…”
Section: Role Of Mir‐29 Family In Osteoporosismentioning
confidence: 99%
“…In 2019, Chen et al reported that ox-LDL/CD36 signaling in macrophage links dysregulated FA metabolism and oxidative stress from the mitochondria, which drove chronic inflammation in the atherosclerosis model [122]. Our group also discovered that miR-29a protects against glucocorticoid-mediated osteoporosis by suppressing the activity of osteoclasts and differentiating from macrophages [128], thus supporting its role in regulating immune cell activity. As a result, CD36 may play a role in linking FA metabolism with mitochondrial oxidative stress and inflammation, as well as be a promising target for reversing hepatic dysfunction in NAFLD.…”
Section: Role Of Mir-29a In Mitochondrial Metabolismmentioning
confidence: 58%